Naming and conceptual understanding in frontotemporal dementia. (November 2019) - Snowden, Julie S.; Harris, Jennifer M.; Saxon, Jennifer A.; Thompson, Jennifer C.; Richardson, Anna M.; Jones, Matthew; Kobylecki, Christopher
Abstract: Behavioural variant frontotemporal dementia (bvFTD) is characterised by behaviour change and impaired executive skills. There is growing evidence that naming difficulties may also be present but the basis for these is unclear. A primary semantic deficit has been proposed, although executive contributions to naming breakdown are also possible. The study aimed to improve understanding of the naming disorder in bvFTD through direct comparison with semantic dementia (SD), and examination of neural correlates. It aimed also to address current controversies about the role of the anterior temporal lobes in semantic memory. We studied 71 bvFTD and 32 SD patients. Naming data were elicited by two picture naming tests (one challenging and one less demanding) and word comprehension by word-picture matching. Structural magnetic resonance images were rated blind using a standardised visual rating scale. Around half of bvFTD patients showed impaired naming and 17% impaired word-picture matching. Deficits in bvFTD were less severe than in SD, but showed a similar pattern. There were strong inverse correlations between naming scores and atrophy in temporal structures, particularly temporal pole and fusiform gyrus. Word comprehension scores correlated more strongly with posterior than anterior temporal lobe atrophy in SD. Error analysis highlighted a significant relationship in both groups between associative-type responses and temporal pole atrophy. By contrast, 'don't know' responses, suggesting a loss of conceptual knowledge, correlated with more posterior temporal regions. There was some correlation in bvFTD between naming and executive test performance but not with frontal lobe atrophy. The findings support the view that naming problems can arise in bvFTD independently of patients' 'frontal' executive impairment and highlight clinical overlap between bvFTD and SD. We discuss the findings in relation to the hub and spoke model of semantic memory and argue against the notion of an anterior temporal lobe semantic hub.